Prices and money in the early modern period in Spain: Fresh evidence from new data, 1492 - 1810 - Emilio Congregado; Vicente Esteve García; María A. Prats; Nicola Rubino (London School of Economics and Political Science (LSE), European Institute, 2024)
In this article, we use as case study the Spanish economy in the Early Modern period. We use recent time series data for the period 1492 - 1810. We consider the possibility that a linear cointegrated regression model with multiple structural changes would provide a good empirical description of the classical model of inflation for Spain over this long period. The principle testable implication is that money growth and inflation are cointegrated, ruling out speculative bubbles in the Spanish inflation rates.
Keywords: C22; E31; E51; N13; 330; Classical model of inflation; Money demand; Money growth; Inflation; Explosiveness; Time-varying volatility; Cointegration; multiple structural changes